Heliodorus’ reading of Lucian’s "Toxaris" - Tagliabue, Aldo (Mnemosyne <Leiden>, 2016)
This article demonstrates that Cnemon’s story in Heliodorus’ Aethiopica intertexts with the novella of Deinias in Lucian’s Toxaris. The closeness of three textual parallels, along with a subtle use of characters’ names, proves that Heliodorus is deliberately recalling Toxaris. The focus of this intertextuality is Chariclea, the courtesan of Deinias’ story. This immoral figure is a striking counterpart to the lustful Demaenete, the main character of Cnemon’s story and the first immoral lover of the Aethiopica. At the same time, the evocation by Heliodorus of a lustful woman who has the same name as the protagonist Chariclea, paradoxically enriches the characterization of the latter as chaste. Furthermore, this subtle evocation of Chariclea seems to have metaliterary implications as well. In the Aethiopica Chariclea stands for the entire novel: Heliodorus appears to define the nature of his text in opposition to Lucian’s Toxaris and to the different kind of fiction it represents. Heliodorus’ definition of his own novel by means of establishing a contrast with other texts is an important function of his intertextuality with Imperial literature and possibly sheds new light on the status of ancient fiction as a whole.
Gesehen am 20.07.2017